THE CORRELATION BETWEEN PEER SUPPORT AND ENGLISH SPEAKING CONFIDENCE AMONG STUDENTS AT THE ELEVENTH GRADE OF SMA NEGERI 1 TEMBILAHAN HULU - Khairunnisa; Edi Ardian; Sri Erma Purwanti (Program Studi Pendidikan Bahasa Inggris, 2025)
The importance of conducting this research is to examine the correlation between peer support and students’ English speaking confidence, highlighting how peer support can help improve students’ confidence in speaking English. English speaking confidence is essential for students’ academic achievement and personal development. However, many high school students still face difficulties in speaking English fluently due to anxiety and lack of self confidence, revealing a gap between the recognized importance of speaking skills and students’ actual performance. This study aimed to investigate the correlation between peer support and English speaking confidence among the eleventh grade students at SMA Negeri 1 Tembilahan Hulu. Using a correlational research design, data were collected from 98 students through Likert scale questionnaires measuring peer support and English speaking confidence. The Pearson Product Moment correlation analysis revealed a correlation coefficient of r = 0,356 which is greater than the critical values at both the 5% (0,195) and 1% (0,256) significance levels. It indicates a low but significant positive correlation between the two variables. Accordingly, the alternative hypothesis (H1) is accepted, and the null hypothesis (H₀) is rejected. Descriptive results showed that while most students perceived high peer support, their speaking confidence was at a moderate level. These findings indicate that peer support positively influences English speaking confidence, but other factors also play a role. Therefore, it is recommended that teachers adopt a comprehensive approach that includes peer support alongside other psychological and contextual strategies to enhance students’ confidence in speaking English.